O cotidiano nas ruas centrais de Pouso Alegre/MG (1880 – 1920) - Andrade, Ana Eugênia Nunes de (2018)
The research titled the daily life in the Central streets of Pouso Alegre-MG (1880- 1920) aims to reflect on the dynamics of the city dipping in the network of social signals in order to understand the trajectories of the subject in everyday life in Pouso Alegre, Minas Gerais, enabling a new historiographical approach. In this research we seek to understand the daily life of various social subjects through the Organization of local urban core and consequently, the social conflicts experienced in the Central streets of the city. As well as understand the ways of life permeated by new urban templates deployed by local governments and the different uses of public spaces for social actors reflecting the ressignificações of the city that have changed through time. From the interpretation of historical sources (newspapers, ads, official documents, photography and works memorialistas) seek to think in existence of a social field where the hegemonic and alternative memories are produced by everyday life. So we understand that memories are social, because they carry the groups organize particularities and share in different ways